Wash-free operation of smartphone-integrated optical immunosensor using retroreflective microparticles - Kim, Ka Ram; Lee, Kyung Won; Chun, Hyeong Jin; Lee, Danbi; Kim, Jae Ho; Yoon, Hyun C. (Biosensors and Bioelectronics, 2022)
Herein, we introduce a smartphone-integrated immunosensor based on non-spectroscopic optical detection. Sedimentation of the retroreflector and gentle inversion of the microfluidic chip was chosen as biosensing principles to ensure minimal human involvement. To realize this, wash-free immunosensing was implemented on a polymeric microfluidic chip device fabricated for light signal penetration in retroreflection signal acquisition. Applying a transparent chip and passive modulation of retroreflectors enabled the minimization of human error during sensing. In addition, a retroreflection-detectable optical gadget was constructed for integration with the commercial smartphone. The gadget had an optical chamber that induced retroreflection by integration with a smartphone. When the micro-sized reflector, named the retroreflective Janus microparticle, reacted on the sensing surface, the incident light was retroreflected towards the image sensor and quantified by a smartphone-installed Android application package. The developed application package features include time-lapse image capture performed by manipulating LED flash and camera modules, and quantification of retroreflected signal counts by image processing of time-lapse images. With this platform, the user could independently commence optical signal processing without a complicated optical setup and running software on a PC, and sensitive and reproducible immunosensing results could be obtained. The applicability test for creatine kinase-myocardial band detection from the buffer to serum was conducted and presented a calibration curve of 0–1000 ng/mL within 1 h. With the developed system, we believe that the applicability of the platform in bioanalytical detection can be expanded.
Keywords: Creatine kinase; Creatine kinase-MB; Immunosensing; Micro particles; Microfluidic-chips; Optical bio-sensing; Retro reflection; Retro-reflectors; Smart phones; Smartphone-based biosensor; Biosensing Techniques; Humans; Immunoassay; Lab-On-A-Chip Devices; Microfluidics; Smartphone; Creatine kinase-MB; Immunosensing; Optical biosensing; Retroreflection; Smartphone-based biosensor